The Educational Achievement of Pupils with Immigrant and Native Mothers: Evidence from Taiwan - Eric S. Lin; Yu-Lung Lu (Institute for the Study of Labor (IZA), 2015)
This paper takes advantage of the Taiwan Assessment of Student Achievement data set to empirically evaluate whether the test score differentials between pupils with immigrant and native mothers are substantial across subjects, grades and years. Our results show that there exist test score differentials between the two groups after controlling for the students' individual characteristics and family background. The Chinese, Math and English subjects exhibit larger test score gaps relative to Science and Society. We also find that the academic gaps between native students and pupils with mothers from Southeast Asian countries tend to widen, while the students' performance is about the same as that for native students if their mothers are from mainland China, confirming that the language proficiency of immigrant mothers significantly affects pupils' learning. Our empirical results may suggest that remedial teaching (or an equivalent preferential policy) for the lower-grade pupils with immigrant mothers might be required to create a fair environment for learning, and such a policy should take the nationality of those foreign mothers into account.
Keywords: A2; I2; 330; foreign spouse; immigrants; academic performance